Assessing performance of Mawar Emas as a mosque-based Islamic financing program - Supiandi Supiandi; Risky Angga Pramuja; Sri Budi Cantika Yuli; Muhammad Yakub; Baiq El Badriati (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2022)
Purpose — This research aims to assess the performance of the Mawar Emas program since its inception.Method — This descriptive qualitative research involves several types of respondents such as mosque administrators, Chairperson of the Masyarakat Ekonomi Syariah (MES), MES Secretary, and beneficiaries. Data obtained through in-depth interviews were processed using reduction, display, triangulation and conclusion techniques.Result — Using primary and secondary data and qualitative research techniques, the authors found that the Mawar Emas initiative supported 32 mosques in West Nusa Tenggara, totaling 1,194 prospective debtors. In terms of funding, the Mawar Emas program has a yearly budget of Rp. 1,275,000,000. However, these funds have not been used to their full potential since the program's inception. There was a decrease in funding and absorption of funds in the program's second year. Several aspects of this program must be evaluated, including increased funding, defaults, training delivery, outdated data, and the presence of profit-oriented institutions.Contribution — This study contributes by providing performance of a mosque-based Islamic financing program to reduce dependency on conventional moneylenders.